Global trends in the research of biodegradable biomedical magnesium-based materials: a bibliometric analysis - Zhu, Yi; Liu, Yuezhu; Wu, Lanping; Yang, Qian (Frontiers in Materials, 2023)
Background: In recent years, there has been a notable surge in the interest surrounding biodegradable materials, particularly in the context of biomedical applications. This has led to a significant rise in the number of research studies focusing on the utilization of biodegradable magnesium-based materials in the field of biomedicine. However, a dearth of comprehensive assessment exists regarding the body of research concerning biodegradable biomedical magnesium-based materials. In this study, a bibliometric approach was used to illustrate the current state of research and global trends pertaining to biodegradable magnesium-based materials for biomedical applications. Method: We conducted a search of the Web of Science core collection database for the past decade (2013–2022). VOSviewer software and the bibliometric online analysis platform were employed for bibliometric analysis and visualization. Results: Correspondingly, 1267 documents were retrieved. We discovered that the number of papers in the field of degradable biomedical magnesium-based materials research has increased annually. In addition, China and the Chinese Academy of Sciences have published the largest number of papers in the field of biodegradable biomedical magnesium-based materials. Papers related to biodegradable magnesium-based materials for biomedical use were mainly published in acta biomaterialia, materials science & engineering c-materials for biological applications and materials journals. Keyword co-occurrence analysis showed that "corrosion"and "mechanical-properties" appear more frequently. The top 10 common keywords include corrosion, mechanical-properties, microstructure, biocompatibility, behavior, magnesium, magnesium alloys, degradation magnesium alloy, in vitro. Conclusion: Research on biodegradable magnesium-based materials for biomedical use continues to increase steadily. China maintains a leading position in the world, and the Chinese Academy of Sciences represents a notable contribution to the research of biodegradable magnesium-based materials for biomedical use. Subsequently, "corrosion" and "mechanical-properties" were identified as the current research hotspots in the area of biodegradable biomedical magnesium-based materials.